Partisipasi Kelompok Nelayan Pesisir Karya Segaradalam Konservasi Terumbu Karang di Pantai Serangan Denpasar - Jaya, Indra (Humanis; Volume 15. No.2. Mei 2016)
Abstract Serangan coast area is now changed because reclamation project by the developer company that willing to build the international tourism area but isn’t happen. These matter makes Serangan’s people participate on the rehabilitation for the coastal area with coral conservation project by Karya Segara coastal fisherman gruop.There are many interest point we could see in Karya Segara coastal fisherman group on their participation for coral conservation. Such as: the reason why they do that, what kind of activity they do, and the result or effect of their participation. The reason why this fisherman group do the coral conservationis because the change of coastal condition that was came from outside and inside the Serangan community. The other reason is the support from the government and non government organization, the social awareness about coastal conservation for the live resources, and the last is from Balinese culture concept about Tri Hita Karana. Karya Segara coastal fisherman group try to rehabilitation the coastal environment by doing the coral transplantation project. More over, they educate people in Serangan how to do coral transplantation, collaborate the tourism activity with conservation (ecotourism) and cooperate with the government organization and commercial company to engage social responsibility. The result or effect of their participation are: 2,5 hectare of coral area, ecotourism activity utilize pontoon, the change of social behavior, employement oppurtinity and also the Kalpataru award on 2011 for save the environment categories from Indonesian government.
Keywords: Change, Adaptation, Participation